Organic dyes containing nonsubstituted aryl amino moieties and azobenzene units for dye‐sensitized solar cells. Issue 9 (22nd July 2019) - Toan, Nguyen Duc; Chiu, Kuo Yuan; Tran, Thai Thi Ha; Yang, Te‐Fang; Su, Yuhlong Oliver
Abstract: A series of novel sensitizers were successfully synthesized utilizing azobenzene as a π‐linkage unit for the D–π–A structure. A slight red shift on the absorption spectra and λonset of the sensitizers could be observed when the thienyl group was introduced to the acceptor moiety (A). In addition, replacing the donor moiety (D) from carbazole to diarylamino could lead to a negative shift (approximately 0.3 V) in the first oxidation potential. DFT calculation was also carried out and the trend of calculated HOMO–LUMO gaps was consistent to the experimental data obtained from the CV results (DT1 < DT2 < DT3 < DT4 ). These sensitizers were then employed in dye‐sensitized solar cells to investigate their photovoltaic performances. Highest power conversion efficiency (PCE) of 0.84% was achieved forDT1 ‐based DSSC according to its most bathochromic absorption spectrum. Abstract : A series of novel sensitizers were successfully synthesized utilizing azobenzene as π‐linkage unit for D‐π‐A structure. A slight red‐shift on the absorption spectra and λonset of the sensitizers could be observed when thienyl group was introduced to the acceptor moiety.